2011
DOI: 10.5603/fhc.2011.0058
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pattern recognition receptors in liver biopsy specimens of children chronically infected with HBV and HCV

Abstract: Abstract: Abstract: Abstract: Pattern recognition receptors (PRRs) constitute a pivotal arm of innate immunity. Their distribution is widespread and not limited to cells of the immune system. Following our previous findings concerning the expression of Toll-like receptors (TLRs) 2, 3 and 4 in chronic viral hepatitis C of children, we wished to search for other PRRs, including other TLRs, NOD-like receptors (NLRs) and RIG-1-like helicase receptors (RLR) in infected hepatocytes. Liver biopsy fragments from ten c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Importantly, NOD1 expression is augmented in hepatocytes of hepatitis C virus patients (68). We now report that, in addition to the acute response to a synthetic ligand and to ectopic expression of the viral polymerase, long-term expression of low levels of all viral proteins in mouse hepatocytes as well as bona fide infection of primary human hepatocytes with HCV also induce NOD1 expression.…”
Section: Discussionmentioning
confidence: 81%
“…Importantly, NOD1 expression is augmented in hepatocytes of hepatitis C virus patients (68). We now report that, in addition to the acute response to a synthetic ligand and to ectopic expression of the viral polymerase, long-term expression of low levels of all viral proteins in mouse hepatocytes as well as bona fide infection of primary human hepatocytes with HCV also induce NOD1 expression.…”
Section: Discussionmentioning
confidence: 81%
“…Expressions of TLRs are found to be increased in severe HBV infections and in cases of cirrhosis (5,12,13,16,30). It is a common finding in the literature that TLR-2 expression significantly increases in HBeAg (-) CHB patients, meanwhile inconsistent results are reported regarding TLR-4 expression (3,9,15,18,21,24,29).…”
mentioning
confidence: 70%
“…The pathogenesis and clinical manifestations of hepatitis B are due to the interaction of the virus and the host immune system. The in vitro and in vivo studies to date show that TLRs can play an important role in the pathogenesis of HBV (9,11,(13)(14)(15)(16)18,20,23,(27)(28)(29)(30). Increased expression of TLR-2 in peripheral blood monocytes and liver biopsy specimens with CHB patients has been shown (14,18,21,24,26,31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although human biopsies provide limited opportunities for mechanistic studies, they are critical since they allow a snapshot view of the tissue that is infected in the actual host. Consistent with this concept, Mozer-Lisewska et al reported that in liver from patients with chronic hepatitis C infection, the expression of TLR1, 2, 4, NALP, and RIG-I helicase was markedly increased, suggesting that these PRRs may be important for the pathogenesis of chronic viral hepatitis by HCV in humans (41). …”
Section: Hepatitis C Virusmentioning
confidence: 85%